2017
DOI: 10.1063/1.4975230
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of hydration of fullerols [C60(OH)n] and hydrogen bond dynamics in their hydration shells

Abstract: Molecular dynamics simulations of fullerene and fullerols [C(OH), where n = 2-30] in aqueous solutions have been performed for the purpose of obtaining a detailed understanding of the structural and dynamic properties of these nanoparticles in water. The structures, dynamics and hydration free energies of the solute molecules in water have been analysed. Radial distribution functions, spatial density distribution functions and hydrogen bond analyses are employed to characterize the solvation shells of water ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 144 publications
0
5
0
1
Order By: Relevance
“…It can be assumed that in this case, the optical anisotropy induced by the magnetic field mainly is owing to the internal anisotropy of the clusters formed by fullerenol C 60 HyFn molecules, which, in turn, is determined by a certain deviation of their shape from spherical. Of course, there is a question about how noticeable this effect is, since the carbon skeleton of this molecule continues to remain the same as that of fullerene C 60 However, according to the results of the simulation carried out in [10], the attachment of a certain amount of OH groups to the core of the C 60 HyFn molecule can form structures with a fairly well-defined asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…It can be assumed that in this case, the optical anisotropy induced by the magnetic field mainly is owing to the internal anisotropy of the clusters formed by fullerenol C 60 HyFn molecules, which, in turn, is determined by a certain deviation of their shape from spherical. Of course, there is a question about how noticeable this effect is, since the carbon skeleton of this molecule continues to remain the same as that of fullerene C 60 However, according to the results of the simulation carried out in [10], the attachment of a certain amount of OH groups to the core of the C 60 HyFn molecule can form structures with a fairly well-defined asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…92 The geometrical and force field parameters of the solvent molecule are given elsewhere. 31 All the bonds of the solute and solvent molecules were kept fixed using the LINCS algorithm. 93 Thus, the solute molecules were treated as rigid species in our simulations.…”
Section: Computational Models and Methodologiesmentioning
confidence: 99%
“…24,25 Solubility of fullerols in aqueous media is dependent on the number of hydroxyl groups as well as the position of the hydroxyl groups. 26,30,31 Labille et al, observed that pristine fullerene can acquire sufficient hydrophilic character by surface hydroxylation in the presence of a solvent. 32 These are some of the most interesting derivatives in fullerene chemistry.…”
Section: For Correspondencementioning
confidence: 99%
“…These carbon nanoparticles are highly soluble in aqueous solution, with reported solubilities as high as 58.9 g/L. , PHFs are known to behave nonideally at higher concentrations, forming aggregates that can be detected by dynamic light scattering. PHF behavior at lower concentrations is less well characterized, although most reports generally assume–either explicitly or implicitly–that PHF solutes are monomers in aqueous solutions having concentrations ≤ 0.1 mg/mL. , Despite the large number of hydroxyl groups decorating the PHF surface, not all hydroxyl groups contribute to aqueous solubility. Numerous experimental and modeling studies report that hydroxyl groups tend to cluster on the fullerene surface where they can be stabilized internally through intramolecular hydrogen bonding. This asymmetry complicates efforts to understand PHF chemistry in aqueous solution and at aqueous interfaces. Simple models describing properties based on functional group additivity will be less effective because not all hydroxyl groups contribute equally to stabilization in solution.…”
Section: Introductionmentioning
confidence: 99%